1976
DOI: 10.1002/star.19760280605
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Corn Starch under the Influence of Gamma Irradiation

Abstract: Irradiation of corn (maize) starch with different doses of gamma irradiation ranging from 1 × 105 rad to 1 × 106 rad resulted in the increase of starch acidity and reducing power. Molecular degradation was observed as a result of marked decrease in starch viscosity and intrinsic viscosity as well as swelling capacity. The gelatinization time and temperature of the irradiated starch became shorter than in the control sample. Internal changes in the irradiated starch occured as a result of lowering the number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

1978
1978
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…1B) were similar to that of the flour. The result was in agreement with the previous reports of the effects of irradiation on pasting viscosities of various starches [2,8,13,[18][19][20][21][22]. The reduction in viscosity indicated that gamma irradiation caused molecular degradation to starch granules.…”
Section: Pasting Viscositysupporting
confidence: 92%
See 1 more Smart Citation
“…1B) were similar to that of the flour. The result was in agreement with the previous reports of the effects of irradiation on pasting viscosities of various starches [2,8,13,[18][19][20][21][22]. The reduction in viscosity indicated that gamma irradiation caused molecular degradation to starch granules.…”
Section: Pasting Viscositysupporting
confidence: 92%
“…Crystallinity of irradiated starch increases with increasing radiation dosages in wheat and rice starches [10,13], and decreased in potato starch [15]. Increase in irradiation dosage decreases viscosity and increases water solubility and acidity of starches [8,13,[18][19][20][21][22]. The gelatinization enthalpy was reported to increase [16,17] or decrease [2,11,15] gradually with increasing irradiation dosage.…”
Section: Introductionmentioning
confidence: 99%
“…Much research has been done on the effects of γ-irradiation on starch properties from various sources (4,(6)(7)(8)(9)(10)(11)(12). There are some reviews available on the properties of irradiated starches (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…The crystallinity of irradiated starch becomes higher with increasing radiation doses in corn and rice starches (7,16). Increased radiation dose is invariably associated with lower viscosity and higher water solubility and acidity of starches among various studies (4,(7)(8)(9)(10)(11)13). Swelling power is generally lowered (7,9), but may become higher under 20 kGy treatment, and then declines rapidly (8).…”
Section: Introductionmentioning
confidence: 99%
“…Starch is degraded by ionizing radiation, resulting in decrease in viscosity (El-Saadany et a!., 1976;Nene et al, 1975;Roushdi et al, 1983). The viscosities of black and white peppers which contain high amounts of starch are lowered by irradiation, and measurement of viscosity has been proposed as a method to detect irradiated black and white peppers (Farkas et al, 1990a, b;Heide and Boegl, 1990;Mohr and Wichmann, 1985).…”
Section: Introductionmentioning
confidence: 99%